คุณภาพของเครื่องมือที่ใช้ในการวิจัย - แสงเลิศอุทัย, จิตติรัตน์ (Journal of Research and Curriculum Development, 2018)
บทความวิชาการนี้มีวัตถุประสงค์เพื่อนำเสนอสาระสำคัญเกี่ยวกับการตรวจสอบคุณภาพของเครื่องมือแต่ละประเภทที่ใช้ในการวิจัยทั้งแบบทดสอบ แบบสังเกต แบบสัมภาษณ์ แบบสอบถาม แบบประเมินการปฏิบัติ ในเรื่องของความเที่ยงตรง ความยากง่าย อำนาจจำแนกและความเชื่อมั่น เพื่อให้นักวิชาการและผู้สนใจสามารถนำไปใช้ในการวิจัย การพัฒนาการเรียนรู้ของผู้เรียนและพัฒนาวิชาชีพได้ The purposes of this article were to present the major of Quality of researchinstrument. The article covered test, observation form, interview form, questionnaireand performance assessment form. Qualified research instrument consisted of validity,reliability, difficulty and discrimination. Application for academic professional andresearcher were for developing their own learning ability and professional works in thefield.